(untitled) (Journal of Legal Studies, 2015)
The defense of the personâ€Ÿs life and health represents a constant concern for all legal systems. The person’s life and health were protected as primary and absolute values of any society in any social regime, and state had the task of creating some mechanisms that would ensure the protection of the social values against some approaches that are not according to the law.